IMPROVING MATHEMATICAL UNDERSTANDING THROUGH ACTION, PROCESS, OBJECT AND SCHEMA BASED DISCOVERY LEARNING MODEL - Handa Maya Sari; M. Ikhsan; Usman (RADJA PUBLIKA, 2023)
Learning that does not encourage students to learn in building knowledge results in weak mathematical understanding skills. The strategy that is expected to foster mathematical understanding skills is through the APOS-based discovery learning model. The purpose of this study was to determine the increase in mathematical understanding skills after receiving learning using the APOS-based discovery learning model, and to determine the interaction between learning and student levels on improving mathematical understanding skills. This study uses a quantitative approach with a pre-test and post-test control group design. The population of this study was grade VIII students of MTsN 1 Aceh Selatan by taking a sample of two classes consisting of an experimental class and a control class. The selection of samples in the study was carried out by random sampling. The instrument used in this study was a mathematical understanding ability test. The data analysis technique in this study used the ANOVA test. Based on the results of the study, it was found that there was a difference in improving students' mathematical understanding skills taught through the application of the APOS-based discovery learning model with conventional learning. Furthermore, the results of this study also identified that there was no interaction between learning and student levels on improving mathematical understanding skills. Therefore, teachers are expected to be able to expand the application of the discovery learning model to other materials without having to look at the background of the students' ability levels because this discovery learning model is suitable for application to all levels of students.